Late-time cosmology with third generation gravitational waves observatories - Souza, Josiel Mendonça Soares de (2023)
With the first detection of gravitational waves in 2015 by the observatories LIGO Hanford and Livingston, a new window opened to the study of astronomy, astrophysics, and cosmology. With gravitational waves emitted by binary systems of compact objects, such as binaries of black holes and neutron stars, we can measure directly their luminosity distances dL, similar to type Ia supernovae called standard candles. Thus, these gravitational wave sources received the name standard sirens, in analogy with the standard candles. If an electromagnetic counterpart of these sources is available, as the signal GW170817, we can identify directly their sky position, and so, their host galaxies and redshifts z. Thus, having a relationship dL − z through detections of gravitational waves with electromagnetic counterparts, we can perform cosmological tests, such as measuring H0, performing Bayesian model selection, and constraining cosmographic parameters, among others. In this work, we explore the strength of the planned ground-based third generation observatories, Einstein Telescope and Cosmic Explorer to probe the evolution of the Universe’s expansion. We start presenting our software GWDALI developed to estimate uncertainties in gravitational wave parameters via Fisher-Matrix and beyond Gaussianity approach of likelihoods. We also explore how much the synergy between third generation observatories can improve measurements of luminosity distances of bright standard sirens (standard sirens with electromagnetic counterparts) to get the best cosmological constants from dL − z relationships. Finally, we deal with the cosmography approach, forecasting the maximum accuracy in the measurements of the first three cosmographic parameters, Hubble constant H0, deceleration parameter q0, and jerk j0 with Einstein Telescope.